Analisis Persepsi Mahasiswa terhadap Tampilan Antarmuka UI/UX pada Web SIAKAD UNISM - Syarifuddin Syarifuddin; Nor Annisa (Universitas Methodist Indonesia, 2026)
The Academic Information System (SIAKAD) is a vital component that supports academic activities at Sari Mulia University (UNISM). This study aims to quantitatively analyze student perceptions of the current quality of SIAKAD's User Interface (UI) and User Experience (UX), particularly in the context of the shift to mobile device usage. The method used was a descriptive survey based on a 5-point Likert Scale questionnaire of 70 active students from various faculties. Crucial results revealed that 94% of students access SIAKAD via smartphones, but the findings show a significant gap between visual quality and technical performance. Basic UI aspects (readability and color) were rated